Prediction of phonological and gender information: an event-related potential study in Italian - Ito, A; Gambi, C; Pickering, MJ; Fuellenbach, K; Husband, E (Elsevier, 2019)
Do people predict different aspects of a predictable word to the same extent? We tested prediction of phonological and gender information by creating phonological and gender mismatches between an article and a predictable noun in Italian. Native Italian speakers read predictive sentence contexts followed by the expected noun (e.g., un incidente: ‘accident’) or another plausible, but unexpected noun, either beginning with a different phonological class (consonant vs. vowel, e.g., uno scontro: ‘collision’; phonological mismatch) or belonging to a different gender class (e.g., un'inondazione: ‘flooding’; gender mismatch). Phonological mismatch articles elicited greater negativity than expected articles at posterior channels around 450–800 ms post-stimulus. In contrast, gender mismatch articles elicited greater negativity than expected articles at left posterior channels around 250–800 ms. Unexpected nouns showed an N400 effect followed by frontal positivity relative to expected nouns. The earlier effect for the gender mismatch articles suggests that people are quicker or more likely to pre-activate gender information vs. phonological information of a predictable word. We interpret the results with respect to production-based prediction accounts.